Mental health problems and risk assessment in football players infected with SARS-CoV-2: a cross-sectional study - Lima, Yavuz; Denerel, Nevzad; Devran, Sergen; Guenver, Mehmet G.; Bayraktar, Bulent; Rice, Simon (Edizioni Minerva Medica, 2022)
BACKGROUND: Although the negative psychological impact of the pandemic on athletes is well known, there is currently insufficient evidence regarding mental health (MH) problems among athletes infected with SARS-CoV-2. The aim of the present study was to evaluate the association between MH problems, demographics, and SARS-CoV-2 related variables in football players infected with SARS-CoV-2. METHODs: An online survey included demographic questions, SARS-CoV-2 related questions, the Athlete Psychological Strain Questionnaire, and the Depression Anxiety Stress Scales-21 was distributed to male and female professional football players aged between 18-38 and infected RESULTS: A total of 261 football players participated in the study. The odds of athlete-specific distress in lower-level football players were up to 5.9 times more than those competing at the highest level (OR=3.06-5.93, 95% CI: 1.27-14.43, P<0.01). The odds of depression and stress in lower-level football players were up to 6.7 times more than those competing at the highest level (both OR=3.70-6.77, 95% CI: 1.18-19.20, P<0.01). In players who reported sleep problems, there was increased risk of athlete-specific distress (OR=2.43, 95% CI: 1.31-4.52, P<0.01), depression (OR=3.71, 95% CI: 1.98-6.95, P<0.01), anxiety (OR=2.93, 95% CI: 1.62-5.28, P<0.01), and stress (OR=7.08 95% CI: 3.52-14.02, P<0.01). There was increased risk of depression and stress in female players (OR=5.78, 95% CI: 2.03-16.4, P<0.01; OR=4.91, 95% CI: 1.5715.4, P<0.01; respectively). The odds of anxiety in players who reported severe SARS-C0V-2 symptoms were up to 2.2 times more than asympCONCLUSIONS: MH problems in football players infected with SARS-CoV-2 were associated with female gender, participation in football in the lower-level, performance concerns, and sleep problems. MH assessment is indicated in athletes infected with SARS-CoV-2 to support detec(Cite this article as: Lima Y, Denerel N, Devran S, Giinver MG, Bayraktar B, Rice S. Mental health problems and risk assessment in football players infected with SARS-CoV-2: a cross-sectional study.
Keywords: Athletes; Soccer; COVID-19; Risk factors